WOMEN EMPLOYABILITY THROUGH SKILL DEVELOPMENT - Bhalla, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Empowerment is the process of increasing the capacity of individuals or group to make choices and transform those choices into desired actions and outcomes. Empowerment of women means developing them as more aware individuals, who are politically active, economically productive and independent and are able to make intelligent discussion in matters that effect them. Women empowerment as a concept,is defined as redistribution of social power and control of resources in favour of women. Skill and knowledge are the driving forces of economics growth and social development of any country.The economy becomes more productive, innovative and competitive through the existence of more skilled human potential. Women are the most vibrant and dynamic segments as well as potentially most valuable human resources. However, despite Phenomenal capabilities, India is seriously handicapped with a very weak and narrow knowledge and skill base with 12.3% gross enrolment ratio, as compared to 21% in china,54.6%in developed countries and the world average is 23.2%.